Oxidative Stress Is Associated with Overgrowth in Drosophila l(3)mbt Mutant Imaginal Discs. - Climent-Cantó, P.; Molnar, C.; Santabárbara-Ruiz, P.; Prieto, C.; Abril, J.F.; Serras, F.; Gonzalez, C. (Cells, 2022)
The loss-of-function conditions for an l(3)malignant brain tumour (l(3)mbt) in larvae reared at 29 °C results in malignant brain tumours and hyperplastic imaginal discs. Unlike the former that have been extensively characterised, little is known about the latter. Here we report the results of a study of the hyperplastic l(3)mbt mutant wing imaginal discs. We identify the l(3)mbt wing disc tumour transcriptome and find it to include genes involved in reactive oxygen species (ROS) metabolism. Furthermore, we show the presence of oxidative stress in l(3)mbt hyperplastic discs, even in apoptosis-blocked conditions, but not in l(3)mbt brain tumours. We also find that chemically blocking oxidative stress in l(3)mbt wing discs reduces the incidence of wing disc overgrowths. Our results reveal the involvement of oxidative stress in l(3)mbt wing discs hyperplastic growth.